Epidemiología y tratamiento de la acarosis en la población de las áreas sub-urbanas de Lima (Pampa de Cueva y El Ermitaño) - De Alarcon, Graciela S. (1973)
As part of field activities in Preventive Medicine for second and third year Medical Students, a 10% survey of the population has been done in a restricted area of Cueva and Ermitaño (marginal communities in the outskitts of Lima). The prevalence of Acarosis in these communities has been found to be 12.5% considering both communities as a whole. This infestation has been found to be more frequent in Cueva than in Ermitaño, in those under 15 years of age, and in women. Possible explanations for these differences are offered and future work is outlines. Emphasis is made on the educational value of the described experience. A combined effort of Cueva and Ermitaño's population and the UPCH Health team resulted in a single day massive treatment of Acarosis (Decenber the 9th, 1972). There were four working groups: Movilization of the community, Diagnosis, Treatment, and Complications. The goal was, to reach 70% of the affected population, which by and large was achieved. The therapeutic agent used was Gamexan which showed an effectivity rate of 70% and a rate of complications of 3.3%. Possible explanations for these findings are discussed and future work is outlines. Emphasis is made on this type of field activities as an effort to give a comprehensive training to the health professional.